2018
DOI: 10.1111/cen.13889
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid activation by 11β‐hydroxysteroid dehydrogenase enzymes in relation to inflammation and glycaemic control in chronic kidney disease: A cross‐sectional study

Abstract: SummaryObjectivePatients with chronic kidney disease (CKD) have dysregulated cortisol metabolism secondary to changes in 11β‐hydroxysteroid dehydrogenase (11β‐HSD) enzymes. The determinants of this and its clinical implications are poorly defined.MethodsWe performed a cross‐sectional study to characterize shifts in cortisol metabolism in relation to renal function, inflammation and glycaemic control. Systemic activation of cortisol by 11β‐HSD was measured as the metabolite ratio (tetrahydrocortisol [THF]+5α‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…However, preliminary proof-of-concept was demonstrated though a reduction in [THF+alloTHF]/THE ratios (the gold-standard measure of systemic 11β-HSD1 activity) and elevated DHEAS consistent with other selective 11β-HSD1 inhibitor trials, including AZD4017 ( 34, 36-39 ). As anticipated, 11β-HSD2 activity was unaffected ( 40, 41 ). The lack of peripheral inhibition was not due to a lack of exposure in situ as skin biopsy AZD4017 correlated with plasma levels, albeit at lower concentrations.…”
Section: Discussionsupporting
confidence: 73%
“…However, preliminary proof-of-concept was demonstrated though a reduction in [THF+alloTHF]/THE ratios (the gold-standard measure of systemic 11β-HSD1 activity) and elevated DHEAS consistent with other selective 11β-HSD1 inhibitor trials, including AZD4017 ( 34, 36-39 ). As anticipated, 11β-HSD2 activity was unaffected ( 40, 41 ). The lack of peripheral inhibition was not due to a lack of exposure in situ as skin biopsy AZD4017 correlated with plasma levels, albeit at lower concentrations.…”
Section: Discussionsupporting
confidence: 73%
“…The latter conversion is of importance for salt regulation, for cortisol has an equal affinity for the mineralocorticoid receptor and thus equal effect as aldosterone, whereas cortisone has no binding potential [25,43,44]. In line with prior research in adults and children, we found that 11β-HSD type 1 activity was negatively correlated with kidney function [45,46]. Also consistent with our data is literature that indicates that the functionality of 11β-HSD type 2 declines over the course of kidney disease [47,48], although some data indicate that this phenomenon might only occur at severely impaired kidney function [49].…”
Section: Discussionsupporting
confidence: 87%
“…The overall daily glucocorticoid production, as measured by the total 24 h urinary excretion of glucocorticoid compounds did not differ between the 2 groups (p = 0.32). In plasma, a significantly lower concentration of cortisone was found (41 vs. 55 [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] nmol/L, respectively, p < 0.001), but not of cortisol (see online suppl. , p = 0.03).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Global 11β-HSD1 activity was evaluated through the quantification of 24-hour urinary glucocorticoid metabolites, by LC–MS/MS ( Sagmeister et al , 2018 ). 11β-HSD1 activity was inferred from the ratio of (5α-tetrahydrocortisol + tetrahydrocortisol):tetrahydrocortisone [(5α-tetrahydrocortisol + tetrahydrocortisol):tetrahydrocortisone] alongside a stable ratio of total urinary cortisol (F):total urinary cortisone (E) reflecting 11β-HSD2 activity ( Tomlinson and Stewart, 2001 ).…”
Section: Methodsmentioning
confidence: 99%